An Underground Passage at Auchencass Castle, Dumfriesshire - Younger, Harry J (Proceedings of the Society of Antiquaries of Scotland, 1931)
An account of a passageway with an oblong chamber at either end is located east of the moat on the east side of the ruined 13th-century castle. Its function and date is uncertain though it is believed to be 18th century.